Important factors for the entrepreneurship in Central Europe - Ján Dvorský; Zora Petráková; Gentjan Çera; Andrea Folvarčna (Innovative Marketing)
The aim of this article is to define and quantify the significant factors (social environment, access to the financial resources and macroeconomic environment), which determine the perception of the entrepreneurial propensity of students for starting a new business in the Czech Republic, the Slovak Republic and Poland in academic year 2016/2017. Empirical research was realized through questionnaire on the basis of 1,352 students (more than 1%level of significance) of the economic universities in the last year of their study in the Czech Republic, Slovak Republic and Poland. The statistical hypotheses were verified using multiple linear regression modelling. The results showed that the entrepreneurial propensity of students in all countries is mostly affected by the social environment. Czech students gave the social environment higher impact on the entrepreneurial propensity for starting a new business than Polish and Slovak students. The results indicate that access to the financial resources is also important for the entrepreneurial propensity of students in the Czech Republic. As for Polish and Slovak students, the access to the financial resources is not a significant factor to the entrepreneurial propensity in their countries. The results having been processed are the basic information for the academic community, public sector, ministry of education in the country, and other organizations whose effort is to help the students to start a new business in her/his country.